Recent advances in the application of nanomaterials for the remediation of arsenic-contaminated water and soil. Issue 4 (August 2021) - Alidokht, Leila; Anastopoulos, Ioannis; Ntarlagiannis, Dimitrios; Soupios, Pantelis; Tawabini, Bassam; Kalderis, Dimitrios; Khataee, Alireza
Abstract: This review specifically deals with the latest advances in the application of nanotechnologies and nanocomposites for remediation of arsenic (As)-contaminated water and soil. Remediation mechanisms generally include physicochemical adsorption and (photo)chemical redox reactions and filtration. Recently, various types of engineered organic/inorganic nanocomposites have been designed in membrane forms, embedded structures, or composites with extraordinary physical-chemical properties, and outstanding capacity for removal or immobilization of As in contaminated sites. In the present article, we give an overview of engineered nanomaterials developed recently (2017–2021) and their interaction mechanisms with As in contaminated water and soil. Emerging approaches include the development of bio-nanocomposites and nanomaterials that show both oxidative and adsorptive capacities. For the first time, we set out to perform a comprehensive assessment of the advantages of nanomaterials in As-contaminated soils with the focus on the mechanisms of decreasing bioavailability and leaching of As. Although great researches have been developed, serious study gaps and a new direction to future researches have been identified. Graphical Abstract: ga1 Highlights: Advances in the environmental monitoring of As using nano-sensors are discussed Recent progress in the application of nanomaterials for As removal are presented Mechanisms of As removal from water and soil using nanocomposites are described Further studies are recommended to fill defined research gaps